Production of edible insects: challenges, opportunities, and perspectives for Costa Rica - Bermúdez-Serrano, Ileana Maricruz; Quirós-Blanco, Ana María; Acosta-Montoya, Óscar (Agronomía Mesoamericana, 2023)
Introduction. Edible insects emerge as an alternative source of protein generated with environmentally sustainable production practices and high nutritional value. The production of insect-based food products has increased globally in recent years and it is expected to continue growing. Costa Rica has a small number of edible insect producers, which has led to growing interest from academia and government entities in promoting the sector. Objective. To present the current market, opportunities, challenges, and perspectives of edible insect production, processing, and marketing internationally and in Costa Rica. Development. The current global market for edible insects is described, the main challenges, and opportunities in their production, processing, and marketing, as well as the sector’s development in Costa Rica. Conclusion. Globally, key challenges in edible insect production include low consumer acceptance, lack of insect production technologies, and inadequate regulatory framework. In Costa Rica, collaborative efforts from academia, the public, and private sectors have established a basic regulatory framework allowing the production of three insect species for human consumption. Costa Ricans are willing to include insects in their diet, but there is still a need to develop better production methods to facilitate the sector growth.